Learning Media of Animation in Elementary School: How to Improve Student's Narrative Writing Skills - Pratiwi, Melinda; Rofii, Agus (Journal of Innovation and Research in Primary Education, 2023)
Writing skill is one of the four language proficiency aspects that students need to possess. However, some previous studies have revealed that students' narrative writing ability is still low. One of the efforts that can be made to address this issue is by using animation as a learning medium. This research aims to examine the extent of the influence of using animation as a learning medium on the narrative writing skill of elementary school students. This study employs a quantitative research method with a quasi-experimental design using the non-equivalent control group design. The research was conducted at SDN Cijati 1 Majalengka. The sample of the study consists of 50 respondents from Grade V students. The research instrument used is a written test through a post-test, and the data analysis technique used is quantitative descriptive analysis. The results of this research show that the narrative writing skill of students in the class that used animation as a learning medium is better than the class that did not use animation as a learning medium. Therefore, animation as a learning medium has a significant effect on developing students' narrative writing skill.